A Green Synthesis of Fe3O4 Nanoparticles with Moringa Oleifera Leaf Extract as Methylene Blue Absorbent - Watuna, Monica Ananda; Dwandaru, Wipsar Sunu Brams; Suparno (JST (Jurnal Sains dan Teknologi), 2025)
This research is motivated by the high content of methylene blue dye waste in waters, which is difficult to overcome with conventional methods. In addition, not many studies develop environmentally friendly methods based on natural materials such as Moringa oleifera leaf extract to synthesize effective absorbent nanoparticles. This study aims to conduct green synthesis of Fe₃O₄ nanoparticles (NPs) using Moringa oleifera leaf extract. In addition, another objective is to test the absorption ability of Fe₃O₄ NPs towards methylene blue dye. The method used in this study is experimental. The experiment began with synthesizing Fe3O4 NPs through green synthesis and their characterization using XRD, FTIR, UV-Vis, and PSA. Next, an absorption test of Fe₃O₄ NPs was carried out against methylene blue solutions with variations in mass of 1 g, 2 g, and 3 g. The results showed the formation of Fe3O4 NPs based on the characterization results of Fe3O4 NP samples. XRD showed no sharp peak at 2 angle indicating that the material structure is amorphous. PSA analysis confirmed the presence of nano-sized material of 196 nm, as much as 34.7%. The FTIR spectrum showed the presence of C–H, C–O, C–C, and C–N functional groups, indicating the success of green synthesis. In addition, the presence of Fe–O functional groups in the range of 570–580 cm¹ also supports the formation of NPs. The results of the UV-Vis test of methylene blue solution that had undergone absorption by NPs showed a significant decrease in sample absorption along with the increase in NP mass, which was reinforced by a visual change in the color of the solution, which became clearer. In conclusion, the synthesis of Fe₃O₄ NPs through green synthesis can be an effective and environmentally friendly method for dye waste treatment. This research has important implications in developing environmentally friendly technologies for handling dye waste in waters, because it shows the potential for utilizing abundant and inexpensive natural materials as reducing agents and stabilizers for pollutant-absorbing nanoparticles.